Hubungan Tingkat Kecemasan dengan Kualitas Tidur pada Masyarakat di Masa Pandemi Covid-19 - Ariyana Pramitha Haryani (2021)
Outbreaks of disease caused by a virus can attack humans. The psychological impact that is more often seen during the Covid-19 pandemic is anxiety, one of the effects of anxiety that often occurs is poor sleep quality during the Covid-19 pandemic. This study aims to determine the relationship between anxiety levels and people's sleep quality during the Covid-19 pandemic. This type of research is analytic, with a cross sectional research design. The sampling technique used in this study is accidental sampling, as many as 103 respondents of household heads aged 20-60 years. This study used the Hamilton Anxiety Rating Scale and Pittsburgh Sleep Quality Index questionnaires. The results showed that there was a relationship between anxiety levels and sleep quality in the community during the COVID-19 pandemic with a p value of 0.000 ≤ 0.05. Useful research for the community can increase knowledge and overcome the anxiety they experience during the Covid-19 pandemic. It is hoped that people who want to find information about Covid-19 through accurate sources such as WHO, the Ministry of Health, and journals. So that people are not easily influenced by information circulating outside that has not been accurately informed, with this the community can reduce the level of anxiety they experience so that people's sleep quality is not disturbed.